A green approach to develop zeolite-thymol antimicrobial composites: analytical characterization and antimicrobial activity evaluation. Issue 5 (May 2022) - Cometa, Stefania; Bonifacio, Maria A.; Bellissimo, Annalisa; Pinto, Loris; Petrella, Andrea; De Vietro, Nicoletta; Iannaccone, Giuseppe; Baruzzi, Federico; De Giglio, Elvira
Abstract: In this work, the development, analytical characterization and bioactivity of zeolite-thymol composites, obtained using wet, semi-dry and dry processes, were carried out in order to obtain sustainable and powerful antimicrobial additives. FT-IR, XRD, DSC, TGA, SEM and B.E.T. analyses were carried out to gain comprehensive information on the chemical-physical, thermal, and morphological features of the composites. GC-MS analyses allowed quantifying the active molecule loaded in the zeolite, released by the functionalized composites and its stability over time. Among the three procedures, the dry approach allowed to reach the highest thymol loading content and efficiency (49.8 ± 1.6% and 99.6 ± 1.2%, respectively), as well as the highest composite specific surface area value, feature which promises the best interaction between the surface of the composite and the bacterial population. Therefore, the bioactive surface of composites obtained by this solvent-free method was assayed for its antimicrobial activity against four microbial strains belonging to Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa and Candida albicans species. The higher antimicrobial activity produced by the solvent-free composite in comparison with that of pure thymol, at the same thymol concentration, was ascribed to the large interfacial contact between the composite and the bacterial target. This feature, together with its enhanced storage stability, suggested that this composite could be employed as effective additives for the development of antimicrobial biointerfaces for food, home and personal care applications. Abstract : Zeolite; Thymol; Antimicrobial activity; Hybrid composite; Surface characterization; Solvent-free process.